Experimental Study of The Effect of Activator Molarity on The Compressive Strength of Fly Ash-Based Geopolymer Concrete from Bengkayang Regency Power Plant - Faraid, Luthi Armey; Herwani, Herwani; Faisal, Faisal; Parabi, Ashraf Dhowian (Fakultas Teknik Universitas Tanjungpura, 2024)
Geopolymer concrete is a form of concrete where Portland cement is substituted with alternative materials like fly ash, rice husk ash, and other silica- and aluminum-rich sources as binders. The research employed an experimental method by preparing geopolymer concrete test specimens using fly ash, NaOH solution, Naâ‚‚SiOâ‚ƒ, fine aggregate, and coarse aggregate. Tests conducted included physical properties (slump test and unit weight) and mechanical properties (compressive strength, split tensile strength, and modulus of elasticity). The results showed a slump range of 130